The impact of emotions on visual-movement performance and effectiveness of competitive activity of elite wrestlers - Korobeynikov, G.; Korobeinikova, L.; Latishev, S.; Shackih, V. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The aim was to study the impact of emotions on visual processing in movement performance and its effects on the competitive activity of elite wrestlers. METHODS: The peculiarities of visual perception in information-processing conditions were studied in connection with the emotions of elite athletes. Nineteen elite athletes, Greco-Roman wrestlers, aged 19-22 years, were examined. The wrestlers completed the following tests: simple visual-motor reaction; reaction to a moving object; perception speed; and a scale of emotion excitability. Consents for research in written form were given by the athletes according to the recommendations of the Ethics Committee for Biomedical Research. RESULTS: The results indicate significant links between anger and certain aspects of visual perception in elite athletes. It is likely that the emotional factor of anger is a hindrance to concentration and attention in athletes resulting in ineffective information processing and leading to a deterioration of visual perception and effectiveness of competitive activity. CONCLUSIONS: Anger, as an affective emotion, is a negative characteristic in the wrestler`s general functional state and potentially jeopardizes his/her competitive performance.